2002
DOI: 10.1097/00005392-200202000-00037
|View full text |Cite
|
Sign up to set email alerts
|

Is Increased Cag Repeat Length in the Androgen Receptor Gene a Risk Factor for Male Subfertility?

Abstract: Increased length of CAG repeats in the androgen receptor gene is not a risk factor for male subfertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
3
19
1
Order By: Relevance
“…Previous studies on CAG repeats in infertile men have reported conflicting results. Some suggested no expansion (Dadze et al, 2000;Sasagawa et al, 2001;Van Golde et al, 2002;Rajpert-De Meyts et al, 2002;Lund et al, 2003;MartinezGarza et al, 2008;Badran et al, 2009), while others reported increased length (but still within the normal range) with respect to controls (Tut et al, 1997;Dowsing et al, 1999;Yoshida et al, 1999;Mifsud et al, 2001;Patrizio et al, 2001;Wallerand et al, 2001;Mengual et al, 2003;Katagiri et al, 2006). Only one study indicated that reduced CAG repeats are closely associated with impaired spermatogenesis in infertile men (Komori et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on CAG repeats in infertile men have reported conflicting results. Some suggested no expansion (Dadze et al, 2000;Sasagawa et al, 2001;Van Golde et al, 2002;Rajpert-De Meyts et al, 2002;Lund et al, 2003;MartinezGarza et al, 2008;Badran et al, 2009), while others reported increased length (but still within the normal range) with respect to controls (Tut et al, 1997;Dowsing et al, 1999;Yoshida et al, 1999;Mifsud et al, 2001;Patrizio et al, 2001;Wallerand et al, 2001;Mengual et al, 2003;Katagiri et al, 2006). Only one study indicated that reduced CAG repeats are closely associated with impaired spermatogenesis in infertile men (Komori et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…18 Extremely long repeats of more than 40 CAG sequences leads to Kennedy's disease, which presents with neuromuscular symptoms, hypogonadism and impaired sperm production. 19 Even within the normal range, that is, between 15-30 repeats, there seems to be a negative correlation between the repeat number and androgen sensitivity, sperm production and fertility. [18][19][20][21] Average number of CAG repeats is inversely correlated with the incidence of prostate cancer in different ethnic groups: African-American men, who have a high incidence of prostate cancer, have shorter mean CAG sequences (mean ¼ 18-19) than Caucasians (mean ¼ 22) and Asians (mean ¼ 23) who have lower and the lowest PC incidences, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…19 Even within the normal range, that is, between 15-30 repeats, there seems to be a negative correlation between the repeat number and androgen sensitivity, sperm production and fertility. [18][19][20][21] Average number of CAG repeats is inversely correlated with the incidence of prostate cancer in different ethnic groups: African-American men, who have a high incidence of prostate cancer, have shorter mean CAG sequences (mean ¼ 18-19) than Caucasians (mean ¼ 22) and Asians (mean ¼ 23) who have lower and the lowest PC incidences, respectively. 22 Some analytical studies have also shown an increased risk of prostate cancer among males with low number of CAG repeats 23,24 although evidence is equivocal.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was then corroborated by several studies from a variety of different ethnic populations including Japanese, Caucasian, North American, French, Israeli, Taiwanese and Spanish (Yoshida et al 1999;Dowsing et al 1999;Mifsud et al 2001;Wallerand et al 2001;Patrizio et al 2001;Madgar et al 2002;Pan et al 2002;Casella et al 2003;Asatiani et al 2003;Mengual et al 2003). However, several others, who have investigated Swedish, Belgian, German, Japanese, Danish, Dutch, Indian, Greek, New Zealander, Finish, Hong Kong Chinese and Italian populations were unable to demonstrate an association (Giwercman et al 1998;Legius et al 1999;Hiort et al 1999;Dadze et al 2000;Sasagawa et al 2000Sasagawa et al , 2001Von Eckardstein et al 2001;Yu and Handelsman 2001;Kukuvitis et al 2002;Rajpert-De Meyts et al 2002;Van Golde et al 2002;Thangaraj et al 2002;Dhillon and Husain 2003;Erasmuson et al 2003;Lund et al 2003;Tse et al 2003;Ferlin et al 2004). Interestingly, a study by Komori et al (1999) has suggested that reduction rather than expansion of the CAG repeat (< 16 repeats) is closely related to impaired sperm production in an infertile Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…decade (Tut et al 1997;Yoshida et al 1999;Dowsing et al 1999;Mifsud et al 2001;Patrizio et al 2001;Wallerand et al 2001;Madgar et al 2002;Pan et al 2002;Asatiani et al 2003;Casella et al 2003;Mengual et al 2003), whereas several others were unable to demonstrate an association (Giwercman et al 1998;Hiort et al 1999;Legius et al 1999;Dadze et al 2000;Sasagawa et al 2000Sasagawa et al , 2001Von Eckardstein et al 2001;Yu and Handelsman 2001;Rajpert-De Meyts et al 2002;Van Golde et al 2002;Thangaraj et al 2002;Kukuvitis et al 2002;Erasmuson et al 2003;Dhillon and Husain 2003;Lund et al 2003;Tse et al 2003;Ferlin et al 2004). Thus, the ethnic background of the population studied may play an important role in the correlation between CAG repeat length and male infertility.…”
mentioning
confidence: 99%